MTHFR 677TT is associated with decreased number of embryos and cumulative live birth rate in patients undergoing GnRHa short protocol: a retrospective study - Hong Zeng; Zefu Liu; Lei Zhang; Nenghui Liu (BMC, 2022)
Abstract Background Whether MTHFR C677T genotype affects pregnancy outcomes following assisted reproductive technology is conflicting. And the role of MTHFR C677T genotype on cumulative live birth has not been reported. This study aims to investigate the effect of MTHFR C677T genotype on cumulative live birth following in-vitro fertilization and embryo transfer (IVF-ET). Methods This is a retrospective cohort study that includes 1173 women undergoing their first IVF-ET. We retrospectively compared the reproductive outcomes among the groups stratified by MTHFR C677T genotypes (677CC, 677CT, 677TT). We performed interaction analysis to detect the factor that interacts with the MTHFR C677T genotype. Poisson regression analyses were used to evaluate the associations between MTHFR C677T genotypes with the number of transferable embryos and the number of good-quality embryos. Cox regression analysis was used to evaluate the association between MTHFR C677T genotypes with cumulative live birth. All regression analyses were adjusted with the confounding factors which may independently impact reproductive outcomes. Results There is a significant interactive effect of MTHFR 677TT genotype with GnRHa protocol on reproductive outcomes (P for interaction<0.05). MTHFR 677TT homozygous mutation was found to impact reproductive outcomes under GnRHa short protocol but not GnRHa long protocol. MTHFR 677TT is significantly associated with decreased number of transferable embryos (p-value=0.028), decreased number of good-quality embryos (p-value=0.005), and decreased cumulative live birth rate (p-value=0.024) in patients undergoing GnRHa short protocol. However, the clinical pregnancy rate, miscarriage rate and live birth rate at the first embryo transfer cycle were not significantly different between the groups under both protocols (p-values>0.05). Conclusions MTHFR 677TT genotype is associated with decreased number of transferable embryos, decreased number of good-quality embryos, and decreased cumulative live birth rate in the first complete cycle in patients undergoing GnRHa short protocol.